The Role of DAF-21/Hsp90 in Mouth-Form Plasticity in Pristionchus pacificus - Sieriebriennikov, Bogdan (Mol Biol Evol, 2017)
Phenotypic plasticity is increasingly recognized to facilitate adaptive change in plants and animals, including insects, nematodes, and vertebrates. Plasticity can occur as continuous or discrete (polyphenisms) variation. In social insects, for example, in ants, some species have workers of distinct size classes while in other closely related species variation in size may be continuous. Despite the abundance of examples in nature, how discrete morphs are specified remains currently unknown. In theory, polyphenisms might require robustness, whereby the distribution of morphologies would be limited by the same mechanisms that execute buffering from stochastic perturbations, a function attributed to heat-shock proteins of the Hsp90 family. However, this possibility has never been directly tested because plasticity and robustness are considered to represent opposite evolutionary principles. Here, we used a polyphenism of feeding structures in the nematode Pristionchus pacificus to test the relationship between robustness and plasticity using geometric morphometrics of 20 mouth-form landmarks. We show that reducing heat-shock protein activity, which reduces developmental robustness, increases the range of mouth-form morphologies. Specifically, elevated temperature led to a shift within morphospace, pharmacological inhibition of all Hsp90 genes using radicicol treatment increased shape variability in both mouth-forms, and CRISPR/Cas9-induced Ppa-daf-21/Hsp90 knockout had a combined effect. Thus, Hsp90 canalizes the morphologies of plastic traits resulting in discrete polyphenism of mouth-forms.